Avenues to Precision Oncology - Alexander Meisel (healthbook TIMES. Oncology Hematology, 2020)
Until recently, the clinical management of cancer heavily relied on anatomical and histopathological criteria, with *ad hoc* guidelines directing the therapeutic choices in specific indications. In the last years, the development and therapeutic implementation of novel anticancer therapies significantly improved the clinical outcome of cancer patients. Nonetheless, such cutting-edge approaches revealed the limitation of the one-size-fits-all paradigm. The newly discovered molecular targets can be exploited either as *bona fide* targets for subsequent drug development, or as tools to precision medicine, in the form of prognostic and/or predictive biomarkers. This article provides an overview of some of the most recent advances in precision medicine in oncology, with a focus on novel tissue-agnostic anticancer therapies. The definition and implementation of biomarkers and companion diagnostics in clinical trials and clinical practice are also discussed, as well as the changing landscape in clinical trial design.